Biocompatible smart cellulose nanofibres for sustained drug release via pH and temperature dual-responsive mechanism. (1st December 2020) - Liang, Yuting; Zhu, Hongxiang; Wang, Lei; He, Hui; Wang, Shuangfei
Graphical abstract: Highlights: A temperature and pH dual-responsive biomass-based smart cellulose nanofibres was designed. The interaction mechanism between temperature and pH was revealed. The smart nanofibres possessed excellent biocompatibility and antibacterial properties. The intelligent nanofibres were used for DOX sustained drug release. Abstract: Biocompatible smart dual-responsive cellulose nanofibres were designed and prepared by grafting a temperature and pH dual-responsive polymer (PEI-NIPAM: polyethyleneimine– N -isopropylacrylamide) on cellulose nanofibres (CNF-COOH). The smart cellulose nanofibres showed good antibacterial activity (above 99%) against Escherichia coli and excellent biocompatibility based on acute systemic toxicity, in vitro cytotoxicity, skin irritation, and skin sensitisation analyses. CNF-PEI-NIPAM showed an excellent dual-response performance to pH and temperature, affording the CNF-PEI-NIPAM aerogel with a high loading capacity (330.12 mg/g) for doxorubicin and a high cumulative release rate (59.45 %) at 37 °C and pH 3. These advantages enable the smart cellulose nanofibres to be applied in the fields of food and biomedicine. Interestingly, the interaction between the collapse and expansion of the dual-responsive polymer molecular chains on the CNF-COOH was revealed based on in situ characterisation of the solid materials, which is valuable for the structural design and application of cellulose-based dual-responsive smart nanofibres.